Ethnonational Identities
XI, 259 p.
Keywords: The prominence of ethnonational identities and movements is of increasing interest and concern in today's world. But the nature and importance of these identities remain ill understood. Ethnonational Identities breaks significant new ground by exploring the complex dimensions of ethnonational identity claims, their political mobilisation, and a wide variety of comparative contexts in which they are found. Including case studies from the Québécois to the Mäori and from Kashmiri nationalism to interethnic competition in the Caribbean, it should be read by all those with an interest or involvement in the fields of ethnicity, nationalism and identity politics.